Reasons for Unwanted Pregnancy among Women of Childbearing Age (15-19 Years) in Jambi Province - Kalsum, Ummi; Listiawaty, Renny; Mohd Awal, Dato Noor Aziah (Kesmas, 2021)
The occurrence of unwanted pregnancy (UP) among women of childbearing age (WCA) has been reported to be increasing in various regions, however, this incidence has not been assessed among the adolescents of 15-19 years age group, in Jambi City. The factors influencing this occurrence includes individual, family, and environmental determinants. This study aimed to determine the prevalence of UP among WCA (15-19 years) in Jambi Province. A cross-sectional design was used, while the participants (307 women aged 15-19 years) were selected in Jambi City and West Tanjung Jabung District, using the Multistage Random Sampling. The analytical method used was the Multiple Logistic Regression of alpha 5%. The results showed that the prevalence of UP among WCA (age 15-19 years) was 1.6%, compared to 50% of those that were married. The dominant factor of UP includes the use of contraceptives with an adjusted-odds ratio of 74.5 (95% CI = 3.58-1,549.02), while the control used were the job of WCA, knowledge, dating behaviour, accesses to information media and health facilities, as well as family education. Therefore, it is suggested that creative, innovative, informative promotions, and education were needed via the social media. Besides, the optimization and strengthening of the Gen-Re go to school program should be carried out, as well as synergizing the cross-sectoral activities, government, private sector, and the community (especially parents).